Everyday Public History. Issue 375 (7th February 2022) - Halstead, Huw
Abstract: Public history is often viewed rather narrowly as something that 'happens' in familiar places at particular moments in time under the watchful eye of a 'professional'. This is the public history of the impact and engagement statement: bounded, controlled, measurable. Conversely, I argue for a more ecumenical, diverse and anarchic understanding of public history. Drawing on observations from oral history, participant observation and digital ethnography, I present public history as something that suffuses the everyday lives of historians and non‐historians alike as they continually construct their own histories through myriad sources and methodologies. This 'everyday public history' is diffuse, noisy, messy, often confusing, sometimes troubling; but never singular, straightforward or authoritative. By studying this everyday public history, historians gain a fuller understanding of the power of the past in society, a greater capacity to comprehend and challenge problematic historical narratives, and a more productive entanglement between their work and people's everyday lives.